Модели транспортных задач и структурно-топологического синтеза при стратегическом управлении логистикой дистрибьюции - Годлевский, И. М.; Пинаева, А. А. (НТУ "ХПИ", 2014)
В работе рассматривается задача конфигурирования логистической сети дистрибьюции товаров массового использования. Проведена декомпозиция всей задачи на две отдельные подзадачи: задача рассеивания; задача консолидации и разукрупнения продукции. Модель первой – задача структурно-топологического синтеза с булевыми переменными. Модель второй – транспортная задача линейного программирования с непрерывными, целочисленными и булевыми переменными. Для их решения использован метод ветвей и границ.

A corporate strategy of the company is shaped from marketing, logistics and production strategies. A strategic goal in the logistics domain consists of several sub-goals, one of which is to configure the logistics network. Models and algorithms for solving transport problems and selecting placement of manufactures and warehouses are used in order to solve the configuration problem. This paper considers the layered structure of the logistics distribution network of two intermediate levels for mass consumer goods, which are presented by disaggregating and consolidating warehouses. The purpose of the work is the development of transport problems models and selection of the intermediate warehouses location due to a given location of a manufacture.
Models of transportation problems and structural-topological synthesis in the strategic management of logistics distribution
Keywords: сбыт товара; распределение товара; логистическая сеть; дистрибьюция; транспортная задача; линейное программирование; метод ветвей и границ; logistic network; distribution; decomposition; transport task; linear programming; method of branches and borders